(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This scientific article explores the effectiveness of game-based strategies in teaching abstract vocabulary to primary school students. Abstract vocabulary (e.g., justice, courage, freedom, emotion) presents a significant challenge in language education due to its lack of physical referents. Traditional rote-learning methods often fail to provide the deep semantic understanding required for young learners. This paper argues that game-based learning (GBL) bridges the gap between concrete experience and abstract conceptualization by leveraging motivation, context, and social interaction. Through a review of constructivist learning theories (Piaget, Vygotsky) and recent empirical studies, this article identifies key game mechanics—such as role-play, storytelling, and digital gamification—that facilitate comprehension. The findings suggest that when abstract words are embedded in meaningful, playful contexts, primary school students demonstrate higher retention rates, improved pragmatic usage, and increased intrinsic motivation.